1978
DOI: 10.1177/00220345780570030101
|View full text |Cite
|
Sign up to set email alerts
|

Plaque Minerals and Caries Experience: Associations and Interrelationships

Abstract: Inverse associations were demonstrated between DMFT and total calcium, phosphorus, magnesium, strontium, potassium, and fluoride concentrations in individual plaques. Lithium, strontium, fluoride, and zinc contents were inversely related to plaque mass. Consistent interdependence patterns between elements indicate the operation of a mineral level regulating mechanism, effective under diverse environmental conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 6 publications
1
28
0
Order By: Relevance
“…Similar results (r = -0.23) were obtained by the same group [Schamschula et al, 1978a] when studying 72 children aged 9.7 to 13 years. Curzon [1985] was also able to demonstrate this relationship (r = -0.83) in addition to the earlier reported negative correlations between [Sr] in water, and in enamel and DMFS scores, reported earlier.…”
Section: Epidemiological Caries Studiessupporting
confidence: 84%
“…Similar results (r = -0.23) were obtained by the same group [Schamschula et al, 1978a] when studying 72 children aged 9.7 to 13 years. Curzon [1985] was also able to demonstrate this relationship (r = -0.83) in addition to the earlier reported negative correlations between [Sr] in water, and in enamel and DMFS scores, reported earlier.…”
Section: Epidemiological Caries Studiessupporting
confidence: 84%
“…Of these, Ca is probably more important as apatite saturation is a function of the Ca ++ ion activity raised to the 5th power. Several epidemiologic studies have found that caries activity is inversely related to Ca and P i levels in plaque [Ashley and Wilson, 1977b;Schamschula et al, 1978;Shaw et al, 1983]. It is likely that high plaque mineral content initially provides protection against enamel dissolution, but as frequent sugar exposures continue this content diminishes and/or newly forming plaque contains less Ca and P i .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some authors have suggested that there is an inverse relationship between the concentrations of these ions in dental plaque and caries experience or increment [Ashley, 1975;Ashley and Wilson, 1977b;Schamschula et al, 1978;Grobler et al, 1982;Shaw et al, 1993].…”
mentioning
confidence: 99%